A feasibility study on the fracture strength measurement of polycrystalline graphene using nanoindentation with a cylindrical indenter. (October 2016) - Han, Jihoon; Ryu, Seunghwa; Sohn, Dongwoo
Abstract: The strength of pristine graphene and its grain boundaries (GBs) are mainly measured by nanoindentation with a spherical tip due to the difficulty of conducting uniaxial tensile tests. However, we recently showed that the fracture forces from the spherical indenter cannot be directly mapped onto the uniaxial strength. In this paper, employing a series of molecular dynamics simulations combined with a fracture mechanics analysis, we demonstrate that the fracture force from cylindrical indenters can be directly mapped onto the strength of graphene under uniaxial tension. Under indentation with cylindrical tips or uniaxial tension, the rupture of graphene sheets that have GBs with a low-tilt angle occurs simultaneously with the onset of crack nucleation at the GBs. On the contrary, when indented by a spherical indenter tip, the graphene sheets sustain the indentation loads until the crack size becomes comparable to the tip radius. Furthermore, the results show that estimating the strength with a cylindrical indenter is not very sensitive to the indentation site as well as angular misalignments that can be caused by human error or the limitations of the apparatus. Our work presents the feasibility of obtaining the tensile strength from nanoindentation experiments, which may suggest a new standard to measure the tensile strength of graphene and related two-dimensional materials.